ADAPTATION OF TESTING PROCEDURES AND STABILIZATION OF RESULTS IN PRESCHOOL RHYTHMIC GYMNASTS - Andrea Marković; Aleksandra Aleksic-Veljkovic; Lucija Milčić; Borko Katanić; Branislav Majkić; Kamenka Živčić (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
The aim of this study was to familiarize preschool rhythmic gymnasts with testing procedures and to determine the number of familiarization attempts needed to stabilize the test results. Thirty-six female rhythmic gymnasts aged 5.14±0.79 years (body height: 119.44±5.98 cm; body mass: 21.46±3.35 kg) volunteered for the study. All gymnasts were free of injury, trained regularly (two days per week, approximately 60 minutes per session), and participated in the individual B level competitions. The main findings indicated a statistically significant difference between the variables of spine and leg flexibility (p<0.00), standing long jump (p<0.00), balance (p<0.00), and shoulder flexion and extension (p<0.00). According to the results obtained in this research, familiarization can significantly improve scores in motor tests for all variables (spine and leg flexibility, balance, standing long jump, and shoulder flexion and extension) in preschool rhythmic gymnasts. These findings suggest several possibilities for further research, such as investigating the long-term effects of familiarization on motor skill development, the specific mechanisms through which familiarization enhances performance, and its impact across different age groups and skill levels in rhythmic gymnastics. Rhythmic gymnastics trainers and other coaches of aesthetic sports should adapt and introduce participants to test protocols to avoid errors in testing.